Analysis of Joint School Section Practice of Private School under Universal Basic Education in Nigeria - Bello, Muhinat Bolanle (STAI Auliaurrasyidin Tembilahan, 2021)
This study examined the threat pose by schools operating a joint section under UBE to academic activities of both the pupils and students. The research method adopted for this study is the qualitative descriptive design of survey type. Upper basic school I, II, and III students of 15 purposively selected schools operating joint section Universal Basic Education System in Ilorin metropolis were selected for the study. Researchers-designed structured interviews with content validity and 0.77 reliability index of the instrument was the only instrument used to elicit the needed data from the respondents. The findings of the study revealed that: upper basic school students were seriously distracted the students it is meant to cater for in many ways. Based on the findings, it was recommended among others that; the same time should be allocated to both sections for both school activities since they use the same compound to decrease distraction and confusion of the students or better still, sections should be structured in different locations to reduce overpopulation in the compound thereby making teaching and learning more effective.